Sunakku Cafe / G Soheana Sulaiman... [et al.] - Sulaiman, G Soheana; Mohd, Mohd Azizi; Yunsai, Listah; Muhammad, Sukri (2014)
Sunakku Cafe is a restaurant located in One Borneo Hypermall, Jalan Sulaman, Kota Kinabalu, 88400, Malaysia: 088-447744 with its address Sunakku Cafe, No. C-205, Concourse Floor, 1 Borneo Hypennall. Sunakku' Cafe serves all levels of social class, gender, age, and income status, and accepts booking for table an hour before the stated time for the necessary preparation as well as walk-ins. Sunakku Cafe serves Japanese-style food such as Ramen, Takoyaki and Japanese style crepes.